Parallel Lines for Calibration of Non-Central Conical Catadioptric Cameras - Bermúdez Vargas, James; Bermúdez Cameo, Jesús; Guerrero, José J. (Jornada de Jóvenes Investigadores del I3A, 2022)
In this paper we propose a new calibration method for non-central catadioptric cameras that use a conical mirror. This method consists of using parallel lines, extracted from a single omnidirectional image, instead of using the typical checkerboard to obtain the calibration parameters of the system.